Microstructure and high temperature mechanical properties of laser rapidly formed Ti-6Al-4V alloy - 薛蕾 陈静 林鑫 吕晓卫 王维 黄卫东 (Transactions of Nonferrous Metals Society of China, 2006)
Several tensile samples were prepared using laser rapid forming （LRF） with Ti-6Al-4V alloy as powder material, and the samples were annealed. The microstructure and high temperature mechanical properties of laser formed Ti-6Al-4V alloy through annealing treatment were investigated. The short-term and long-term tensile tests at 350 ℃ were performed. The results show that the microstructure of LRF samples consists of the large columnar prior β grains which grow epitaxially from the substrate along the deposition direction. There are Widmanstaitten a laths in prior β grains, but a laths in annealed microstructure are coarser, and their aspect ratio is lower than that in as-deposited microstructure. In addition, the prior β grain boundary is also coarsened and broken off through the annealing treatment. The high temperature mechanical properties of the annealed LRF samples exceed those of casting alloy significantly, especially the stress-rupture lifetime reaches 661.7 h even while the test stress increases from initial value of 490 MPa to the final stress of 800 MPa gradually.